Prediction of Gestational age by Last Menstrual Period (LMP) in Comparison to Ultrasonography (USG) - Ghani, Afroza; Nahar, Aftabun; Sultana, Nasrin; Khatun, Ashiya; Sultana, Rifat; Yusuf, Md Abdullah; Zakaria, Rooh E (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Accurate dating is cardinally important for good pregnancy care. USG provides accurate dating of GA and has now days become an essential part maternal antenatal care. Objective: The purpose of the present study was to identify LMP as a better method for predicting the day of delivery than the USG measurement. Methodology: This was a Hospital-Based prospective, comparative study conducted at both inpatient and outpatient Department of Obstetrics and Gynaecology at Chittagong Medical College Hospital, Chittagong from October 2007 to September 2008 for a period of one year. The study populations were pregnant women with certain LMP and had dating USG at Nuclear Medicine Centre, Chittagong performed in first or early second trimester 12 - 14 weeks. Result: Among the 112 patients, 61 patients delivered within i 7 days of EDD based on LMP; whereas 82 patients delivered within 1 7 days of EDD based on USG. Of these, actual day of delivery of 49 patients correlated with the same gestational week determined by both LMP and USG. Actual day of delivery of 18 among these 112 patients did not correlate with the EDD determined either by LMP or USG and they all delivered beyond i 7 days of EDD based on either LMP or USG. Conclusion: USG dating during the estimated GA range of 12 to 14 weeks gave a more accurate prediction of delivery date than the estimate based on LMP. J Shaheed Suhrawardy Med Coll, 2014; 6(2):82-86